Ruiz Figueroa, Manuel (coord.), El islam y Occidente desde América Latina, México, El Colegio de México, 2007, 319 pp. - Hodara, Joseph (Estudios de Asia y África, 2008)
Ruiz Figueroa, Manuel (coord.), El islam y Occidente desde América Latina, México, El Colegio de México, 2007, 319 pp.